KEMAMPUAN MENULIS PUISI SISWA SMA - Nadia Dclara (Teks: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2021)
This study aims to obtain information whether or not there is a relationship between the mastery of language style and students' creativity together with the ability to write poetry in class X SMAN 84 Jakarta, which can be detailed as follows: 1) There is a relationship between the mastery of language style and the ability to write poetry. class X student of SMAN 84 Jakarta; 2) There is a relationship between creativity and the ability to write poetry in class X SMAN 84 Jakarta; and 3) There is a relationship between mastery of language style and creativity with the ability to write poetry in class X SMAN 84 Jakarta. The population in this study were 7 classes, namely class X MIPA 1 s.d. X MIPA 3, X IPS 1 s.d. X IPS 3, and X IBB. This study took a sample of 20% of the population with a total of 80 students from two classes selected randomly, namely class X MIPA 1 and X MIPA 3. This research is a quantitative research analyzed using the SPSS version 23 application. The results of this study indicate that there is a relationship. which is significant between Language Style and Poetry writing skills because t arithmetic (5.745) is greater than the t table price (1.664). The results of this study indicate that there is a significant relationship between creativity and poetry writing skills because tcount (6.150) is greater than the t table price (1.664). There is a relationship between mastery of language style and creativity with the ability to write poetry in class X SMAN 84 Jakarta with a determination coefficient of R2y (1,2) of 0.500, which means that language style and creativity can jointly influence 50% change in the variable of poetry writing skills (Y).